The Effect of Sintering Conditions on the Microstructure and Electrical Properties of Pb(Zr0.52Ti0.48)O3 Ceramic - Wan Azhar, Wan Yusoff; Nur Shafiza Afzan, Sharif; Julie J., Mohamed; Hutagalung, Sabar Derita; Zainal Arifin, Ahmad; Mohd Zulkifly, Abdullah; Hasmaliza, Mohamad (Faculty Mechanical Engineering, UMP, 2014)
Lead zirconate titanate Pb(Zr0.52Ti0.48)O3, (PZT) from mixture of commercial PbO, TiO2 and ZrO2 powders were successfully prepared using planetary ball mill. The microstructure and electrical properties of PZT ceramic were found to be more sensitive to the sintering condition. The influence of microstructure and electrical properties towards sintering condition of the samples were studied. SEM analysis indicated that shorter sintering time with higher sintering temperature promotes fine structure and densification. This have been proves where relative density of the obtained sintered PZT ceramics was measured to be approximately 99 % of the theoretical density. The electrical properties of the ceramic sintered at higher temperature with different sintering time were measured at high frequencies. The result revealed that different sintering conditions give big impact to the electrical behavior in a broad frequency region.